Optimizing Microstrip Antenna Miniaturization Using U-Slot and L-Slot Techniques for Enhanced L-Band Performance - Harianto, Bambang Bagus; Suprapto, Yuyun; Pambudiyatno, Nyaris; Irfansyah, Ade (International Journal of Artificial Intelligence Research, 2025)
Rapid advances in wireless communication systems have increased the demand for compact and efficient antennas. This study presents the design and analysis of miniature microstrip antennas intended for applications in L-band frequencies. The antenna structure is based on a rectangular patch with modifications in the form of U-shaped slot (MRDPU) and L- shaped slot (MRDPL) configurations that aim to reduce the size of the antenna without sacrificing performance. The proposed antenna operates in the frequency range of 1,064 GHz to 1,562 GHz, with significant improvements in return loss values, bandwidth, and overall efficiency. Comparative analysis shows that the design with U-shaped slots (MRDPU) provides better miniaturization and performance compared to L-shaped slot designs (MRDPL). The U- shaped slot design achieves a return loss of -11.15 dB at 1.064 GHz, while the L-shaped slot design has a return loss of -10.907 dB at 1.206 GHz. Both configurations offer an effective solution for L-band frequency applications. The study highlights the potential of slot-based modifications in achieving antenna miniaturization without sacrificing important performance parameters.